Metodika obucenija junych tjaželoatletov pravil'nomu dychaniju pri vypolnenii sorevnovatel'nych upražnenij - Ilichyova, O. V.; Sirakovskaya, Y. V.; Zavyalov, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article is devoted to the development of the technique for teaching young weightlifters how to breathe correctly when performing competitive exercises, which includes a set of the general and special breathing exercises. The application of this technique provides the opportunity to influence the process of coordination of breathing patterns of the athletes and the structure of competitive exercises at the stage of initial training of the young weightlifters. Rational breathing regimes of the young weightlifters are offered when performing such competitive exercises as jerk and push. The effectiveness of the experimental technique was confirmed during the experiment: the parameters of external respiration improved, both at rest and when performing the competitive exercise (jerk), the number of realized competitive attempts characterizing the level of technical skill increased.